Implementasi Strategi Dinas Koperasi dan UKM Kota Surakarta dalam Pengembangan Sektor Usaha Mikro Kecil dan Menengah (UMKM) - Taufik Ardhiansyah; Retno Suryawati (Program Studi Ilmu Administrasi Negara Fakultas Ilmu Sosial dan Politik Universitas Sebela, 2022)
This study aims to analyze the implementation of the strategy of the Department of Cooperatives and SMEs in the development of the MSME sector in Surakarta City. This research is a qualitative descriptive study using interview, observation, and documentation data collection techniques. Determination of informants in this study using purposive sampling and data validity using triangulation method. Meanwhile, in data analysis, this research uses Miles and Huberman data analysis techniques. The results showed that the implementation of the strategy of the Surakarta City Cooperatives and SMEs in developing the MSME sector had been carried out quite well, but there were still obstacles such as the lack of openness of SMEs in providing business data, the lack of completeness of product legality, and the existence of the Covid-19 pandemic. The development of the Surakarta City Cooperatives and SMEs Service program in the midst of the pandemic situation was focused on the empowerment and development program for MSMEs with activities including MSME monitoring and evaluation, information dissemination on capital providers, entrepreneurship training, promotional exhibitions, trade contacts, and business meetings. The budget for the Cooperatives and SMEs Service is sourced from the Surakarta City Budget, which in the midst of the Covid-19 pandemic is experiencing a budget refocusing. The budget development has been allocated quite well and is able to support the financing of the MSME development program. The Department of Cooperatives and SMEs in developing procedures has compiled the stages of procedures for each program of MSME development activities that also act as a form of supervision of the implementation of these activity programs.